Efeitos das compras públicas na renda de agricultores familiares no Brasil: Análise do programa de aquisiç\~ao de alimentos e do programa nacional de alimentaç\~ao escolar - Lilian de Pellegrini Elias; Jo\~ao Pedro Sim\~oes Magro; Juliane da Silva Ciríaco; Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study evaluates the two main national programs for public purchases of products from family farming in Brazil: the Food Acquisition Program (PAA) and the National School Feeding Program (PNAE). The proposed objective was to analyze the impact of these programs on the income of suppliers in the public procurement markets. To this end, the purchase databases made in each of the programs were cross-referenced with the administrative records of family farmers. Positive and significant effects on the average increase in farmers' income were identified in both programs evaluated, as evidenced by the average treatment effect model. These effects were felt across different income quantiles, being more intense in those with lower incomes, that is, precisely those most interested in the policies. Therefore, the association of these programs with the increase in the income of family farmers are relevant descriptions of the potential of public procurement in the country.
Keywords: Q18; Q12; C23; 330; public procurement; family farming; evaluation of government programs; food and nutritional security; rural development